A democracia na perspectiva filosófica de Norberto Bobbio e Jürgen Habermas. - Tenório, Eljo Farias (2023)
Norberto Bobbio, political and legal philosopher, writer, historian and Italian senator, was born in Turin/Italy, on October 18 1909 and died in his hometown on January 09 2004. Bobbio became remarkably known for his great ability to generate concise,logical and, at the same time, dense writings. This paper aims to present, albeit briefly, Bobbio's thinking on democracy analyzing the author's different convictions on the subject investigating the historical evolution of the democratic doctrine: the democracy of the ancients and the democracy of the moderns; the dichotomy between real democracy and ideal democracy; ethics and procedure; the representative and the direct, until reaching what the Turin philosopher called unfulfilled promises by democracy, as the model of a centripetal society, where people participate in political decisions; fiduciary representation; the end of oligarchic power; the occupation of decision-making spaces by the people; the end of invisible power; and education for citizenship, as well as the causes for non-compliance with these promises, according to its understanding. Also emphasizing the thought of the Italian philosopher on the rise of democratic regimes around the world, despite the setbacks demonstrated in his reflections. The philosophical aspects of convergence and main differences between the representative democracy of Norberto Bobbio and the deliberative (participatory) democracy of Jürgen Habermas are also on focus. Habermas, a philosopher and sociologist born in Düsseldorf, Germany, on June 18 of 1929, which continues in full activity, based on his theories about communicative action, deliberative politics on public sphere, taking contemporaneity as an analytical focus, notably the use of virtual tools as instruments of modern democracy, underlining Bobbio's disbelief on the subject and Habermas' considerations about the possibilities of rescuing the Agoras of ancient Athens through current social networks, keeping the pertinent adaptations and the observance of the validity criteria of the deliberative practice.